Respuesta :
Hey there! :)
For this, you have to use the Pythagorean Theorem.
a² + b² = c² is the same as c² - a² = b²
c = 26
26² = 26 × 26 = 676
a = 10
10² = 10 × 10 = 100
676 - 100 = 576
√576 = 24
b = 24 cm
Hope this helps :)
For this, you have to use the Pythagorean Theorem.
a² + b² = c² is the same as c² - a² = b²
c = 26
26² = 26 × 26 = 676
a = 10
10² = 10 × 10 = 100
676 - 100 = 576
√576 = 24
b = 24 cm
Hope this helps :)
Hello!
Use the Pythagorean Theorem: a² + b² = c² which is also the same as c² - a² = b²
c = 26
26² = 676
a = 10
10² = 100
676 - 100 = 576
The square root of 576 is 24
Your answer is 24 cm
I hope this helps you and have a great day!
Use the Pythagorean Theorem: a² + b² = c² which is also the same as c² - a² = b²
c = 26
26² = 676
a = 10
10² = 100
676 - 100 = 576
The square root of 576 is 24
Your answer is 24 cm
I hope this helps you and have a great day!